Korea : problems and issues in a rapidly growing economy - Hasan, Parvez; World Bank. (Baltimore : Published for the World Bank [by] the Johns Hopkins University Press, 1976)
This book provides a basis for discussions with the Korean government concerning policy decisions. It examines trends and levels of economic factors and its analysed issues involved in alternative policy options. Policies to promote domestic savings, reduce foreign indebtedness, and ensure a balance between import substitution and export production are seen as essential to achievement of a more equitable distribution of growth benefits and a reduction of the economic imbalance between rural and urban areas in Korea.
Includes index.
lje 20/09/2018
Loans
Keywords: Economic history; Commerce; Korea (South); Korea